2010
DOI: 10.1111/j.1466-8238.2010.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic and climatic impacts on surface pollen assemblages along a precipitation gradient in north‐eastern China

Abstract: Aim To understand the scenarios of 'anthropogenic biomes' that integrate human and ecological systems, we need to explore the impacts of climate and human disturbance on vegetation in the past and present. Interactions among surface pollen, modern vegetation and human activities along climate and land-use gradients are tested to evaluate the natural and anthropogenic forces shaping the modern vegetation, and hence to aid the reconstruction of vegetation and climate in the past. This in turn will help with futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 30 publications
2
30
1
Order By: Relevance
“…The studied sites were located in variety of vegetation zones, including desert, steppe, meadow and forest. The vegetation type of each site was assigned according to field investigation and regional vegetation literatures (ISTXCAS and IBCAS, 1978;Wu, 1980;Zhang, 2007). Mean annual temperature (MAT) and mean annual precipitation (MAP) of studied sites referred to the Earth Systems Modelling Results of Bristol Research Initiative for the Dynamic Global Environment (http://www.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studied sites were located in variety of vegetation zones, including desert, steppe, meadow and forest. The vegetation type of each site was assigned according to field investigation and regional vegetation literatures (ISTXCAS and IBCAS, 1978;Wu, 1980;Zhang, 2007). Mean annual temperature (MAT) and mean annual precipitation (MAP) of studied sites referred to the Earth Systems Modelling Results of Bristol Research Initiative for the Dynamic Global Environment (http://www.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of pollen assemblages of topsoils (Liu et al, 1999;Zhang et al, 2010;Zhao et al, 2012a) suggested that high AP/NAP ratios were always found in forest zones and zones with forest patches in northern and northwestern China. The investigation of the pollen assemblages of surface lake sediments in the eastern Tibetan Plateau indicated that a much higher AP/NAP ratio occurred in the patchy forested areas (Herzschuh, 2007).…”
Section: Pollen Ratios Vegetation and Climatementioning
confidence: 99%
See 3 more Smart Citations